Kur’an-ı Kerim’de haram hükümlerin ortaya çıkışı ve konuları - Yılmaz, Nuray (My University, 2006)
Bir yerde düzen ve disiplin varsa orada mutlaka bazı sınırlamalar da var demektir. Çünkü düzen fikriyle başıboşluk bir arada bulunamaz.İslam tutum ve davranışlara sınırlamalar getirirken birey ve toplumun sağlığını huzr ve mutluluğunu esas almıştır. Yüce Allah iyi ve temiz şeyleri helâl kılmıştır.Haramlar ise gerek insan sağlığı ve gerekse toplum açısından zararlı olan, Allah katında sevimsiz olan iş ve davranışlardır. Haram kılma yetkisi Allah’a aittir. Haramlar sınırlı olup, kulları harama muhtaç etmeyecek kadar çok helâl vardır. Haram yapılmaması istenen ve faili zemmedilen fiildir. Hanefiler yapılmaması istenen fiil zanni delille sabit olduğu durumları tahrimen mekruh, Cumhur ise haram olarak nitelendirmektedir. Haram kötülük vasfının o eylemin özünden veya onu çevreleyen şeylerden kaynaklanmasına göre iki çeşittir. Kur’an-ı Kerim haramları bir defada ortaya koymak yerine aşama aşama ortaya koymuştur. Böylelikle insanların Kur’an-ı Kerim’in oluşturduğu düzene kolay bir şekilde geçiş yapmaları sağlanmıştır.

If there exist some orders and disciplines in a place, then this means, there are some restrictions too because the idea of disorder can not be together with the idea of order. While Islam brings some restrictions to the attitudes and behaviours. It takes into consideration the health; peace and happyness of the individual and the society.The Great God says, the good and clean things are permissiple. In contrast the forbidden things are the works and behaviours Which are dangerous for the health of individual and also for society. It’s God Who classifies things as permissible or forbidden. The forbidden things are limited and there are lots of permissible things in order not to make people need forbidden things. Forbidden things are the things that shouldn’t be done. Hanefies considers the situation as (tahrimen) disgusting when the forbidden things are statle with the doubtful proof but Cumhur considers them as forbidden. There exist two kinds of forbidden things. One of them comes from the action itself and the other one comes from the actions that circulate that action. Qur’an made people aware of these forbidden things gradually not quickly thus, thids helps people to get used to the system that Qur’an set.
Keywords: İslam Hukuku; Kur’an-ı Kerim